2014
DOI: 10.1177/000313481408000622
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Clinical Trial of Surgical Intervention for Painful Rib Fracture Nonunion

Abstract: We performed a prospective clinical trial of resection with or without plate fixation for symptomatic rib fracture nonunion three or more months postinjury with 6-month postoperative followup. The McGill Pain Questionnaire (MPQ) and RAND 36 Health Survey were administered and activity level (sedentary, ambulatory, moderately active, vigorous), functional status (disabled, nonphysical labor, physical labor), and work status (employed, unemployed, retired, student) were queried pre- and postoperatively. Twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 25 publications
0
36
0
1
Order By: Relevance
“…It has been suggested that all patients with flail chest or more than four rib fractures who are 45 years of age or older should be treated surgically (107). Intercostal nerve entrapment can lead to chronic pain due to fracture nonunion and can be treated with resection with or without plate fixation (108). A detailed discussion of surgical stabilization is beyond the scope of this article.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…It has been suggested that all patients with flail chest or more than four rib fractures who are 45 years of age or older should be treated surgically (107). Intercostal nerve entrapment can lead to chronic pain due to fracture nonunion and can be treated with resection with or without plate fixation (108). A detailed discussion of surgical stabilization is beyond the scope of this article.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…However, there was no change in functional or work status overall. They did find that patients treated with resection and plating had superior results to resection alone with statistically significant subjective improvement in chronic pain and activity tolerance [30] . Additionally, Gauger et al performed a retrospective study that evaluated the outcomes of 10 patients with 16 symptomatic rib nonunions treated with reconstruction using iliac crest autograft and tension band plate with a locked precontoured plating system [31] .…”
Section: Nonunionmentioning
confidence: 99%
“…This pain can be debilitating and may decrease respiratory effort resulting in atelectasis and pneumonia. Fabricant et al and Gauger et al have recently shown surgical fixation of symptomatic nonunion is a viable option for management [30,31] .…”
Section: Indicationsmentioning
confidence: 99%
See 2 more Smart Citations